An Analysis of Preserving Imaginative and Mythological Elements in Indonesian Lyrics Translation - Miftahul Hidayatulloh; Syamsurrijal Syamsurrijal; Muhammad Zaki Pahrul Hadi (Insan Kreasi Media, 2025)
This study investigates the preservation of imaginative and mythological components in the Indonesian translation of J.R.R. Tolkien's